Adherence to iron supplementation among anemic pregnant women during 1964-2022: A bibliometric analysis - Atmadani, Rizka Novia; Irham, Lalu Muhammad; Perwitasari, Dyah Aryani; Akrom, Akrom; Urbayatun, Siti (Public Health of Indonesia, 2023)
Background: High maternal morbidity and mortality are brought on by the worldwide public health issue of iron and folic acid deficient anemia. The risk to pregnant women’s and their unborn children’s health is reduced when they correctly get and take iron and folic acid supplements. However, people’s inability to adhere to the supplement frequently results in an immense burden. Objective: This analysis focused on describing the field of adherence to iron among pregnant mothers with anemia using bibliometric analysis of the literature from 1981 to 2022 and on analyzing the scientific trends. Methods: We used Scopus as the search engine, using the keywords: Adherence OR Compliance AND Pregnancy OR Pregnant women AND Iron OR Ferrous AND anemia. English journal articles from journals were selected. Results: We retrieved 360 documents during 1981-2022. The result showed trends topics mentioned, mostly pregnancy, anemia, and iron supplementation. The most published articles were from Australia and USA, with Quartal 1 source as the most relevant journal. Conclusion: Although the quantity of publications has increased regularly, it remains below 40 each year. The topic intervention or experimental study, or adherence were still low. Some countries with significantly increased anemia in the last ten years, with the number of publications and collaboration studies remaining high. The modest number indicates that researchers still have many chances to develop better, more productive techniques to enhance adherence and decrease anemia.